Prime-Boost Strategies in Mucosal Immunization Affect Local IgA Production and the Type of Th Response - Fiorino, Fabio; Pettini, Elena; Pozzi, Gianni; Medaglini, Donata; Ciabattini, Annalisa (Frontiers in Immunology, 2013)
Combinations of different delivery routes for priming and boosting represent vaccination strategies that can modulate magnitude, quality, and localization of the immune response. A murine model was used to study T cell clonal expansion following nasal or subcutaneous priming, and secondary immune responses after boosting by either homologous or heterologous routes. T cell primary activation was studied by using the adoptive transfer model of ovalbumin-specific transgenic CD4+ T cells. Both nasal and subcutaneous immunization efficiently elicited, in the respective draining lymph nodes, primary clonal expansion of antigen-specific CD4+ T cells that disseminated towards distal lymph nodes (mesenteric and iliac) and the spleen. After boosting, a very high serum IgG response was induced in all groups independent of the combination of immunization routes used, while significant levels of local IgA were detected only in mice boosted by the nasal route. Mucosal priming drove a stronger Th1 polarization than the systemic route, as shown by serum IgG subclass analysis. IFN-gamma production was observed in splenocytes of all groups, while prime-boost vaccine combinations that included the mucosal route, yielded higher levels of IL-17. Memory lymphocytes were identified in both spleen and draining lymph nodes in all immunized mice, with the highest number of IL-2 producing cells detected in mice primed and boosted by the nasal route. This work shows the critical role of immunization routes in modulating quality and localization of immune responses, in prime-boost vaccine strategies.